User Behavior Evaluation in Robot-Assisted Retinal Surgery - He, Changyan (ROMAN, 2018)
Retinal microsurgery is technically demanding and requires high surgical skill with very little room for manipulation error. The introduction of robotic assistance has the potential to enhance and expand a surgeon’s manipulation capabilities during retinal surgery, i.e., improve precision, cancel physiological hand tremor, and provide sensing information. However, surgeon performance may also be negatively impacted by robotic assistance due to robot structural stiffness and nonintuitive controls. In complying with robotic constraints, the surgeon loses the dexterity of the human hand. In this paper, we present a preliminary experimental study to evaluate user behavior when affected by robotic assistance during mock retinal surgery. In these experiments user behavior is characterized by measuring the forces applied by the user to the sclera, the tool insertion/retraction speed, the tool insertion depth relative to the scleral entry point, and the duration of surgery. The users’ behavior data is collected during three mock retinal surgery tasks with four users. Each task is conducted using both freehand and robot-assisted techniques. The univariate user behavior and the correlations of multiple parameters of user behavior are analyzed. The results show that robot assistance prolongs the duration of the surgery and increases the manipulation forces applied to sclera, but refines the insertion velocity and eliminates hand tremor.